The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jvim.15897
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined carprofen and omeprazole administration on gastrointestinal permeability and inflammation in dogs

Abstract: Background: Proton pump inhibitors (eg, omeprazole) commonly are administered concurrently with nonsteroidal anti-inflammatory drugs (NSAIDs; eg, carprofen) as prophylaxis to decrease the risk of gastrointestinal (GI) injury. However, evidence to support this practice is weak, and it might exacerbate dysbiosis and inflammation. Hypothesis/Objectives: To evaluate the effect of carprofen alone or combined with omeprazole in dogs. We hypothesized that coadministration of omeprazole and carprofen would significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…This is consistent with a report in dogs hospitalized in the ICU in which prophylactic administration of gastro-protectants was associated with a significantly increased risk of development of hemorrhagic GI disease ( 35 ). The most common adverse effect associated with PPI administration in dogs is diarrhea ( 42 44 ), but other more serious complications including intestinal dysbiosis and subsequent bacterial pneumonia are possible ( 25 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a report in dogs hospitalized in the ICU in which prophylactic administration of gastro-protectants was associated with a significantly increased risk of development of hemorrhagic GI disease ( 35 ). The most common adverse effect associated with PPI administration in dogs is diarrhea ( 42 44 ), but other more serious complications including intestinal dysbiosis and subsequent bacterial pneumonia are possible ( 25 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also growing evidence in people and dogs that concurrent administration of PPIs and NSAIDs can increase the risk of GI injury, permeability and inflammation, though this does not necessarily translate to clinical GI signs in all cases ( 45 , 51 , 52 ). While our results demonstrated that more dogs receiving both NSAIDs and prophylactic PPIs developed GI signs (46%) compared to either individually (41 and 30%), this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence that PPIs are more effective for management of acid-related disorders [ 12 ], our study reveals that a considerable number (16%) of Portuguese GPs consider H 2 RAs as a preferable choice. We hypothesize that this could be related to the following: (1) H 2 RAs can provide immediate clinical relief, while PPIs can take longer to reach a peak of action [ 15 , 17 ]; (2) PPIs are a more recent drug, while H 2 RAs were historically used among the Portuguese veterinary community; (3) H 2 RAs have additional cytoprotective effects such as increased mucus and bicarbonate secretion [ 15 ]; (4) H 2 RAtherapies are well tolerated in dogs and cats, with a good safety profile [ 38 ]; and (5) recent studies show potential adverse effects of long-term PPI therapies in cats [ 39 ], as well as documented interactions of PPIs with other drugs [ 40 ]. Nevertheless, it is important to acknowledge the fact that H 2 RAs are weaker acid suppressants and have proven to be less effective for controlling acid-related problems [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“… 30 Therefore, abnormal microbial conversion of luminal substrates by normal microbiota can be pathologic, not just changes in bacterial populations. While some of the microbiome changes that likely originate in the small intestine can be detected in fecal samples, as reported for dogs receiving omeprazole, 23 , 31 dogs with EPI, 32 and dogs with chronic enteropathies (CE), 33 , 34 the above limitations should nevertheless be considered when analyzing fecal samples only.…”
Section: Assessment Of the Intestinal Microbiome—general Considerationsmentioning
confidence: 99%